Software Process Improvement and Capability Determination 12th International Conference, SPICE 2012, Palma, Spain, May 29-31, 2012. Proceedings - Mas, Antonia; Mesquida, Antoni; Rout, Terry; O$1 (BConnor, Rory V.s; Dorling, Alec.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 12th International Conference on Software Process Improvement and Capability Determination, SPICE 2012, held in Palma de Mallorca, Spain, in May 2012. The 21 revised full papers presented and 14 short papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on organizational process improvement; SPI in small and very small enterprises; process models; SPI in automotive software and security; SPI in medical and safety critical systems; short papers.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information systems; Information Systems; Computer Science; Management of Computing and Information Systems; Software Engineering; Computer Communication Networks; Computers and Society; Algorithm Analysis and Problem Complexity; Computer Appl. in Administrative Data Processing